Impact of Al-Najebiya thermal energy power plant on aquatic ecosystem of Garmat Ali canal. - A. Hussein, Sadek; J. Al-Shawi, I.; M. Abdullah, A. (University of Thi-Qar Journal of Science, 2009)
Monthly variations in concentrations of nutrients (nitrite, nitrate, phosphate and silicates) along with total dissolved solids (TDS) were investigated in Al-Najebiya electricity power generating station (N.S).The study extended from November 1997 to October 1998. Three sites were selected for sampling, based on intake and discharge points. The lowest nitrite value (0.15 µg at. N/L) was encountered in November and the highest (1.37 µg at. N/L) in January. Nitrate (NO3) revealedconsiderable rise in concentrations near effluent, as well, and the highest (34.95 µg at. N/L) was in August. Maximum value of phosphate (4.75 µg at. P/L) was encountered near the effluent discharging point. Silicate (SiO3) concentration was also distinctly high in this site, the maximum value (201.1 µg at. Si/L) recorded in August. TDS exhibited higher concentrations in sites closer to thermal discharge as well (1675mg/L). No previous ecological, long or short term, work of the type was recorded for the investigated site or any other similar locations in the country.